Whole-Brain Afferent Inputs to the Caudate Nucleus, Putamen, and Accumbens Nucleus in the Tree Shrew Striatum - Rong-Jun Ni; Rong-Jun Ni; Yu-Mian Shu; Tao Li; Tao Li; Jiang-Ning Zhou (Frontiers Media S.A., 2021)
Day-active tree shrews have a well-developed internal capsule (ic) that clearly separates the caudate nucleus (Cd) and putamen (Pu). The striatum consists of the Cd, ic, Pu, and accumbens nucleus (Acb). Here, we characterized the cytoarchitecture of the striatum and the whole-brain inputs to the Cd, Pu, and Acb in tree shrews by using immunohistochemistry and the retrograde tracer Fluoro-Gold (FG). Our data show the distribution patterns of parvalbumin (PV), nitric oxide synthase (NOS), calretinin (CR), and tyrosine hydroxylase (TH) immunoreactivity in the striatum of tree shrews, which were different from those observed in rats. The Cd and Pu mainly received inputs from the thalamus, motor cortex, somatosensory cortex, subthalamic nucleus, substantia nigra, and other cortical and subcortical regions, whereas the Acb primarily received inputs from the anterior olfactory nucleus, claustrum, infralimbic cortex, thalamus, raphe nucleus, parabrachial nucleus, ventral tegmental area, and so on. The Cd, Pu, and Acb received inputs from different neuronal populations in the ipsilateral (60, 67, and 63 brain regions, respectively) and contralateral (23, 20, and 36 brain regions, respectively) brain hemispheres. Overall, we demonstrate that there are species differences between tree shrews and rats in the density of PV, NOS, CR, and TH immunoreactivity in the striatum. Additionally, we mapped for the first time the distribution of whole-brain input neurons projecting to the striatum of tree shrews with FG injected into the Cd, Pu, and Acb. The similarities and differences in their brain-wide input patterns may provide new insights into the diverse functions of the striatal subregions.